Adenocarcinoma of lung masquerading as systemic auto-immune disease - Naha, Kushal (BMJ Publishing Group, 2012)
A 40-year-old previously healthy male presented with acute onset painless dimness of vision in both eyes since the past week and low-grade fever, anorexia and weight loss for the past 1 month. He had been evaluated at a local hospital and diagnosed to have a posterior cerebral artery territory infarct on the left side on the strength of cranial CT. Shortly after receiving antiplatelets and warfarin he had developed severe coagulopathy as evidenced by haematemesis, epistaxis and haematuria. Preliminary investigation revealed prolonged clotting parameters, renal failure and anaemia. Cerebral MRI showed multiple areas of cortical haemorrhage. In the course of his hospital stay, he developed further stigmata of auto-immunity including Coomb’s positive haemolytic anaemia, recurrent venous thromboses and a palpable purpuric truncal rash. He was eventually diagnosed to have an adenocarcinoma of the lung, and was subsequently referred to an oncologist for further therapy.